Genesis and prospects of the shortage of specialist physicians in Italy and indicators of the 39 schools of hygiene and preventive medicine. - Pennisi , Flavia; Minerva, Massimo; Dalla Valle, Zeno; Odone, Anna; Signorelli, Carlo (Acta Biomedica Atenei Parmensis, 2023)
Background and Aim: In Italy, the number of physicians decreased in recent years due to retirements not being replaced by young specialists. To address this shortage of medical personnel, proper planning is needed, taking into consideration the number of accesses in medical schools and residency contracts. The main objective of this study is to deepen the data on the number of physicians, provide a prospective picture and make some suggestions for future planning. Materials and Methods: Estimates of the number of physicians, contracts, assignments, and abandonments for specialist schools are based on data from the General Medical Council, the Ministry of University and Research, Eurostat and the “Associazione Liberi Specializzandi”.   Results: Estimates of the number of physicians for the period 2023-2032 predict the minimum availability of active doctors between 2028 and 2029. While there has been an increase in the number of contracts for residents in recent years, there are concurrently high dropout rates and non-assignment of contracts, varying across Schools of Specialization. An examination of the available data for the 39 Schools of Specialization in Hygiene and Preventive Medicine shows lower than-average abundance rates. Conclusions: In recent decades, poor planning and early retirement have led to a shortage of doctors, particularly specialists, that will not be resolved until after 2030. Proposed solutions to this 'health emergency' include importing doctors from abroad, delaying the retirement age, recruiting junior doctors to the National Health Service and changing the distribution of junior doctor contracts.